Functional divergence of the duplicated BrrCBL2.1 and BrrCBL2.2 genes in turnip (Brassica rapa var. rapa) - Qingwen Zeng; Haotong Kang; Xiangxiang Kong; Yifan Cai; Zhiyu Chen; Fanfan Lin; Tianping Huang; Yunqiang Yang; Xin Yin; Yanling Yue; Yongping Yang (Plant Gene, 2026)

An on-axis integrated microfluidic chemiluminescence immunoassay platform for rapid multiplex biomarker quantification - Qingjin Wu; Yujian Liu; Hailin Wu; Chenglong Wang; Quandong Li; Yongping Lin; Jiao Yang; Peng Li; Yingchun Li (Chemical Engineering Journal, 2026)

Battery swapping mode analysis for shared e-bikes from a carbon perspective - Yonggang Shen; Chenhan Lin; Yancun Song; Qing Yu; Yongping Zhang (Environmental Impact Assessment Review, 2026)

Divergent drivers of the microbial methane sink in three grassland transects and grassland types in the Northern hemisphere - Yuxiang Hu; Qiang Lin; Yanjiao Liu; Zhe Feng; Chaonan Li; Lin Xu; Xiangzhen Li; Yongping Kou (Journal of Environmental Management, 2026)

Acquisition and temporal transcriptomic characteristics of cambial meristematic cells in Camptotheca acuminata under in vitro culture conditions - Yundan Xiong; Shuang Yu; Jiale Sun; Zhiyu Chen; Fanfan Lin; Yifan Cai; Tianping Huang; Xin Yin; Yan Zheng; Yunqiang Yang; Xiangxiang Kong; Yongping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Retardation of phosphorus release from modified biochar through targeted Fe-Nx-P chemisorption bonding - Conghui Zhang; Wei Liu; Kang Liang; Feng Liu; Kai Meng; Wentao Jiao; Yongping Shan; Hai Lin (Journal of Environmental Management, 2026)

Low phosphorus promotes caryophyllene biosynthesis by regulating AaTPS3 in Artemisia argyi - ZhongWen Ma; Ping Lu; Quan Gu; ShiMin Zhang; ZhiYuan Feng; YongPing Cai; Lin Liu (Plant Cell Reports, 2026)

Regulation of microbial interactions and metabolite profiles via inoculation with Lactiplantibacillus plantarum in naturally fermented young ginger pickles - Ming Yang; Yongqi Chen; Siying Zhu; Hongjian Zhang; Lin Zhang; Jiamu Kang; Yongping Xin (Food Bioscience, 2025)

Molecular mechanisms and therapeutic application of pyrogallic acid in treating multidrug-resistant Klebsiella pneumoniae infections in American bullfrogs (Aquarana catesbeiana) - Han Lin; Furong Li; Yufang Huang; Yongping Ye; Ziyan Chen; Chun Liu; Ruiai Chen (Aquaculture, 2025)

A novel quasi-homogeneous microfluidic platform integrated maintenance-free magnetic electrochemiluminescence sensor for alpha-fetoprotein detection - Shengwei Yang; Yingying Xu; Fuyu Zhou; Yan Li; Hanif Ur Rahman; Yongping Lin; Guanghui Zhang; Le Li; Jiang Liu; Yingchun Li (Chemical Engineering Journal, 2025)

Does bike-sharing support the development of 15-minute cities? A case study of Zhejiang Province, China - Yongping Zhang; Wenyan Fu; Hui Kong; Diao Lin (Sustainable Cities and Society, 2025)

Improving the moving-grid permafrost model to reveal ground deformation and hydrothermal effects caused by permafrost evolution in the source region of the Yangtze river on the Qinghai-Tibet plateau - Zhe Sun; Lin Zhao; Guojie Hu; Shibo Liu; Yongping Qiao; Erji Du; Defu Zou; Guangyue Liu; Lingxiao Wang; Jianting Zhao (Environmental Modelling & Software, 2025)

Demethoxycurcumin induces metabolic crisis and ATF4/ATF3/CHOP-dependent cell death in hepatocellular carcinoma - Fugen Shangguan; Hongfei Zhou; Huachang Zhang; Thaiyuri Reddy; Mhaka Panashe Bryan; Ri Cui; Jianhu Lin; Yongping Chen; Yihu Zheng (Chemico-Biological Interactions, 2025)

Linking Water Technologies with Water Practices: Case Studies from 11 Countries - Lin Gan; Yongping Wei; Shuanglei Wu (Water Resources Management, 2025)
Radical transformations of technology development are required to meet the rapidly increasing global water resource challenges. A systemic understanding of the impacts of water technologies on water practices across countries remains limited. This paper aims to develop an understanding of the linkages between water technologies and water practices in the 11 countries where 95% of the world’s water patents were produced. The water technological development was assessed by both the contents (different types of technologies) and the structure (the technology network). The water practices were presented by country-level indicators representing their water demand, water supply, and water management collected from public databases. It was found that there was an extremely uneven distribution with the top 3 countries (China, Korea, Japan) accounting for over 70% of the total patents, and there were slow growth rates and even a decline of water technologies. All countries demonstrated homogeneous technological development focusing on water supply, and their networks had limited brokerage capacity for knowledge diffusion. Australia, China, Canada, France, and Korea had relatively good links between water technologies and practices, whereas the majority of countries demonstrated unbalanced technological structures with a de-linking to water practices. These findings can assist in developing water technologies for improving water practices in future.

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

Widely targeted metabolomics bridges the sensory characteristics and bioactive components of three typical Lonicera japonica flower tea - Xiangui Mei; Yongping Lu; Lin Zhang; Chuanzhi Kang; Yingying Cui; Lixia Zhang; Jianhua Wang; Zhenqiao Song (Food Chemistry, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Combining metabolomics to analyze the effects of cell wall component and stone cells on fruit texture in Dangshan pear - Pengcheng Wei; Xianang Wu; Xiaofeng Feng; Ping Lu; Yongping Cai; Lianping Wei; Lin Liu (Horticulture, Environment, and Biotechnology, 2025)

The distribution of soil alkaline phosphatase (phoD) gene harbouring bacteria across Qinghai-Tibet Plateau - Lin Xu; Jiabao Li; Chaonan Li; Yongping Kou; Minjie Yao; Changting Wang; Weidong Kong; Junming Wang; Xiangzhen Li (Soil Ecology Letters, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Relationship between shared micromobility and public transit: The differences between shared bikes and shared E-bikes - Hui Kong; Hao Chao; Wenyan Fu; Diao Lin; Yongping Zhang (Journal of Transport Geography, 2025)

Nap1 is essential for eupyrene spermatogenesis and migration in Plutella xylostella - Chenxu Zhu; Lijun Zhou; Dongbin Chen; Xu Yang; Lu Zhu; Lansa Qian; Xiaomiao Xu; Gangqi Fang; Awawing A. Andongma; Yongcheng Dong; Lin He; Yongping Huang; et al. (Insect Biochemistry and Molecular Biology, 2025)

Process and mechanism analysis of typical permafrost area surface deformation at two sites along the Qinghai-Tibet highway based on long-term leveling observation - Shibo Liu; Lin Zhao; Lingxiao Wang; Defu Zou; Guojie Hu; Zhe Sun; Huayun Zhou; Yongping Qiao (Science of The Total Environment, 2024)

Weld distortion prediction of the Cargo Transfer Vessel key structure by fuzzy finite element model and inherent strain theory - Zhijie Zhou; Shupeng Cai; Ming Qiu; Yongping Zhao; Yongkang Zhang; Chaohui Lin (Ocean Engineering, 2024)

Ternary stabilization strategies for succinonitrile-based in situ polymerized electrolyte enabling high-performance solid lithium metal batteries - Chenyu Lin; Tianqi Yang; Haiyuan Zhang; Donghuang Wang; Wenkui Zhang; Yao Wang; Yang Xia; Hui Huang; Xinhui Xia; Yongping Gan; Xinping He; Xinyong Tao; et al. (Chemical Engineering Journal, 2024)

Phosphorus and selenium compounding mitigates Cr stress in peanut seedlings by enhancing growth homeostasis and antioxidant properties - Hongliang Yin; Yongping Jing; Yunqing Lin; Ningning Song; Haiying Zong; Fangli Wang; Shaojing Li; Xin Song; Hong Hou; Yuxian Shang Guan; Quanli Zong; Jun Liu (Environmental Science and Pollution Research, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Spatio-temporal variation in soil thermal conductivity during the freeze-thaw period in the permafrost of the Qinghai–Tibet Plateau in 1980–2020 - Liu Wenhao; Li Ren; Wu Tonghua; Shi Xiaoqian; Wu Xiaodong; Hu Guojie; Zhao Lin; Yao Jimin; Wang Dong; Xiao Yao; Shi Jianzong; Ma Junjie; et al. (Science of The Total Environment, 2024)

Directional guiding of mass and charge transfer via vertically aligned graphite nanosheets for high-rate and ultralong lifespan Dual-ion batteries - Lin Shang; Bi-Yun Shi; Xianchun Liu; Tian-Tian Zhang; Hanlin Liu; Yongping Zheng; Wei-Dong Dou; Qingguang Pan; Yongbing Tang (Chemical Engineering Journal, 2024)

The spatiotemporal variations of freezing index and its relationship with permafrost degradation over the Qinghai–Tibet Plateau from 1977 to 2016 - Ren Li; Junjie Ma; Tonghua Wu; Qinxue Wang; Xiaodong Wu; Lin Zhao; Shenning Wang; Guojie Hu; Wenhao Liu; Yongliang Jiao; Jimin Yao; Yao Xiao; et al. (Theoretical and Applied Climatology, 2024)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Functional analysis of a dirigent protein AtsDIR23 in Acorus tatarinowii - Zihui Guo; Wei Xu; Dongyi Wei; Siyan Zheng; Lin Liu; Yongping Cai (Journal of Plant Physiology, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Chain hybridization‐based CRISPR‐lateral flow assay enables accurate gene visual detection - Meng Cheng; Caiwei Tan; Bo Xiang; Weihong Lin; Bolin Cheng; Xuechun Peng; Yihao Yang; Yongping Lin (Analytica Chimica Acta, 2023)

Two monolignoid biosynthetic genes 4-coumarate:coenzyme A ligase (4CL) and p-coumaric acid 3-hdroxylase (C3H) involved in lignin accumulation in pear fruits - Yunpeng Cao; Yu Chen; Lin Zhang; Yongping Cai (Physiology and Molecular Biology of Plants, 2023)

Polyamide/polyethylene thin film composite (PA/PE-TFC) NF membranes prepared from reverse-phase interface polymerization (RIP) for improved Mg(II)/Li(I) separation - Qingyi Wang; Yongping Dong; Junmei Ma; Huimin Wang; Xuping Xue; Chaojie Bai; Mingjie Lin; Lingping Luo; Congjie Gao; Lixin Xue (Desalination, 2023)

Evaluation of CLM5.0 for simulating surface energy budget and soil hydrothermal regime in permafrost regions of the Qinghai-Tibet Plateau - Junjie Ma; Ren Li; Hongchao Liu; Zhongwei Huang; Tonghua Wu; Xiaodong Wu; Lin Zhao; Guojie Hu; Yao Xiao; Yongliang Jiao; Wenhao Liu; Shenning Wang; et al. (Agricultural and Forest Meteorology, 2023)

Dexmedetomidine Alleviates Lipopolysaccharide-Induced Hippocampal Neuronal Apoptosis via Inhibiting the p38 MAPK/c-Myc/CLIC4 Signaling Pathway in Rats - Yongping Chen; Lin Li; Jiuyan Zhang; Hailin Cui; Jiucheng Wang; Chuqiao Wang; Mingxian Shi; Honggang Fan (Molecular Neurobiology, 2021)

Complete genome analysis of the newly isolated Shigella sonnei phage vB_SsoM_Z31 - Bingdong Wei; Cong Cong; Lichun Zhang; Lin Zheng; Long Chen; Wei Yu; Yongping Xu (Archives of Virology, 2021)

Estimation of surface energy fluxes in the permafrost region of the Tibetan Plateau based on in situ measurements and the surface energy balance system model - Jimin Yao; Lianglei Gu; Cheng Yang; Hao Chen; Jiemin Wang; Yongjian Ding; Ren Li; Lin Zhao; Yao Xiao; Yongping Qiao; Jianzong Shi; Caiping Chen (International Journal of Climatology, 2020)
The surface energy balance is a key issue in land surface process research and important for studies of climate and hydrology. In this paper, the surface energy fluxes (net radiation, ground heat flux, sensible heat flux and latent heat flux) at the Tanggula (TGL) and Xidatan (XDT) sites were measured and the distributions of the regional surface energy fluxes on the Tibetan Plateau were obtained using a revised surface energy balance system (SEBS) model. The results show that the surface energy fluxes have obvious seasonal variations. At both sites, the sensible heat flux is highest in spring and lowest in summer, and the latent heat flux is highest in summer and lowest in winter. The high elevation, snow cover, freeze–thaw process, precipitation, vegetation and soil texture are important influencing factors for land surface energy fluxes. The time‐phase difference between the net radiation and ground heat flux for bare soils is estimated to be 2–3 hr. The ratio of ground heat flux and net radiation ranged from approximately 0.18 to 0.33, and a parameterization scheme for the remote sensing of ground heat flux over the Tibetan Plateau bare soil in summer is developed. The simulation results of the regional surface energy fluxes show that the distributions of surface parameters, such as vegetation, soil texture and soil moisture content, are important for understanding regional changes in the surface energy fluxes.

Strategic Environmental Assessment with the Penetration of Electric Vehicles in Transport Network - Hongzhi Lin; Yongping Zhang (Environmental Modeling & Assessment, 2020)

Metabolomics analysis of nitrogen-containing metabolites between two Dendrobium plants - Cheng Song; Chunyan Jiao; Qing Jin; Cunwu Chen; Yongping Cai; Yi Lin (Physiology and Molecular Biology of Plants, 2020)

Correction to: Particulate matter 2.5 induced arrhythmogenesis mediated by TRPC3 in human induced pluripotent stem cell-derived cardiomyocytes - Cheng Cai; Min Ling; Jiayi Huang; Yongping Lin; Weilun Miao; Pei Chen; Xing Chen; Jiaxian Wang; Minglong Chen; Qian Bian (Archives of Toxicology, 2019)

Family-1 UDP glycosyltransferases in pear (Pyrus bretschneideri): Molecular identification, phylogenomic characterization and expression profiling during stone cell formation - Xi Cheng; Abdullah Muhammad; Guohui Li; Jingyun Zhang; Jun Cheng; Jingxiang Qiu; Taoshan Jiang; Qing Jin; Yongping Cai; Yi Lin (Molecular Biology Reports, 2019)

Particulate matter 2.5 induced arrhythmogenesis mediated by TRPC3 in human induced pluripotent stem cell-derived cardiomyocytes - Cheng Cai; Jiayi Huang; Yongping Lin; Weilun Miao; Pei Chen; Xing Chen; Jiaxian Wang; Minglong Chen (Archives of Toxicology, 2019)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Systematic analysis and comparison of the PHD-Finger gene family in Chinese pear (Pyrus bretschneideri) and its role in fruit development - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Dynamically-downscaled projections of changes in temperature extremes over China - Junhong Guo; Guohe Huang; Xiuquan Wang; Yongping Li; Qianguo Lin (Climate Dynamics, 2018)

Cloning and characterization of DoMYC2 from Dendrobium officinale - Yanfang Zhu; Cancan Meng; Liqin Zhu; Dahui Li; Qing Jin; Cheng Song; Yongping Cai; Honghong Fan; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Mechanism-based QSAR Models for the Toxicity of Quorum Sensing Inhibitors to Gram-negative and Gram-positive Bacteria - Dali Wang; Zhifen Lin; Zhengyang Huo; Ting Wang; Zhifeng Yao; Yongping Cong (Bulletin of Environmental Contamination and Toxicology, 2016)

Molecular cloning and expression of 1-deoxy-d-xylulose-5-phosphate synthase and 1-deoxy-d-xylulose-5-phosphate reductoisomerase in Dendrobium officinale - Honghong Fan; Qiuju Wu; Xiang Wang; Linsong Wu; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Modeling permafrost properties in the Qinghai-Xizang (Tibet) Plateau - GuoJie Hu; Lin Zhao; XiaoDong Wu; Ren Li; TongHua Wu; ChangWei Xie; QiangQiang Pang; Yao Xiao; WangPing Li; YongPing Qiao; JianZong Shi (Science China Earth Sciences, 2015)

Modeling hydrothermal transfer processes in permafrost regions of Qinghai-Tibet Plateau in China - Guojie Hu; Lin Zhao; Ren Li; Tonghua Wu; Xiaodong Wu; Qiangqiang Pang; Yao Xiao; Yongping Qiao; Jianzong Shi (Chinese Geographical Science, 2015)

Variations of DNA methylation and genes expression for brown fiber during its development process - Zhenpeng Li; Tingchun Li; Honghong Fan; Ning Guo; Xu Sun; Yongping Cai; Yi Lin (Acta Physiologiae Plantarum, 2014)

Geographic distance and pH drive bacterial distribution in alkaline lake sediments across Tibetan Plateau - Jinbo Xiong; Yongqin Liu; Xiangui Lin; Huayong Zhang; Jun Zeng; Juzhi Hou; Yongping Yang; Tandong Yao; Rob Knight; Haiyan Chu (Environmental Microbiology, 2012)
Summary Continent‐scale biogeography has been extensively studied in soils and marine systems, but little is known about biogeographical patterns in non‐marine sediments. We used barcode pyrosequencing to quantify the effects of local geochemical properties and geographic distance for bacterial community structure and membership, using sediment samples from 15 lakes on the Tibetan Plateau (4–1670 km apart). Bacterial communities were surprisingly diverse, and distinct from soil communities. Four of 26 phyla detected were dominant: Proteobacteria , Bacteroidetes , Firmicutes and Actinobacteria , albeit 20.2% of sequences were unclassified at the phylum level. As previously observed in acidic soil, pH was the dominant factor influencing alkaline sediment community structure, phylotype richness and phylogenetic diversity. In contrast, archaeal communities were less affected by pH. More geographically distant sites had more dissimilar communities ( r = 0.443, P = 0.030). Variance partitioning analysis showed that geographic distance (historical contingencies) contributed more to bacterial community variation (12.2%) than any other factor, although the environmental factors explained more variance when combined (28.9%). Together, our results show that pH is the best predictor of bacterial community structure in alkaline sediments, and confirm that both geographic distance and chemical factors govern bacterial biogeography in lake sediments.

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Effects of exogenous nitric oxide on antioxidation and DNA methylation of Dendrobium huoshanense grown under drought stress - Honghong Fan; Tingchun Li; Lei Guan; Zhengpeng Li; Ning Guo; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton - Tingchun Li; Honghong Fan; Zhengpeng Li; Jun Wei; Yi Lin; Yongping Cai (Acta Physiologiae Plantarum, 2012)

Inhibition of ATIR by shRNA prevents collagen synthesis in hepatic stellate cells - Peihong Dong; Fujun Yu; Xufei Fan; Zhuo Lin; Yongping Chen; Ji Li (Molecular and Cellular Biochemistry, 2010)

Prognostic factors and recurrence of hepatitis B-related hepatocellular carcinoma after argon-helium cryoablation: a prospective study - Chunping Wang; Yinying Lu; Yan Chen; Yongyi Feng; Linjing An; Xinzhen Wang; Shuhui Su; Wenlin Bai; Lin Zhou; Yongping Yang; Dongping Xu (Clinical & Experimental Metastasis, 2009)

Comparison of human post-embryonic, multipotent stem cells derived from various tissues - Baijun Fang; Ning Li; Yongping Song; Quande Lin; Robert Chunhua Zhao (Biotechnology Letters, 2009)

Dual regulation of the ATP-sensitive potassium channel by activation of cGMP-dependent protein kinase - Yongping Chai; Yu-Fung Lin (Pflügers Archiv - European Journal of Physiology, 2008)